Undergraduate Module for Complementary Medicine and Integrative Health - El Olemy, Ahmed Tawfik (Highlights on Medicine and Medical Science Vol. 5, 2021)
Background: Medical education has undergone major transformation along with the change in concept of health and disease. Objective: Increasing awareness, improving knowledge and acquiring skills of complementary medicine and integrative health for undergraduate medical students. Methods: Complementary medicine and integrative health module was introduced during the year 2016-2017, for fourth year medical students at Dar Al Uloom University, Riyadh, KSA. The Methods of teaching and learning include interactive lectures, seminars, practical sessions, assignments, field visits, simulation, learning by doing (hands on training), case studies, problem based learning and self-directed learning. Topics covered during the course include; Introduction and overview of Complementary and Alternative Medicine (CAM), Epidemiology of CAM practices, Characteristics and comparison of CAM vs. Conventional Medicine, Integrative Medicine, Research models in CAM, Evidence based CAM, Medical ethics of CAM, Frauds and misconceptions related to CAM practices and products, Health education and communication in CAM, Manipulative and body based practices, Biological-based practices, Mind-body medicine, Energy based therapies, Whole medical systems; Traditional Chinese Medicine (TCM), Unani, Arabic or Hakim Medicine, Prophetic Medicine and Local traditional CAM therapies (Hijamah as a model), Acupuncture, Herbal Medicine, Naturopathy, Nutrition and food supplements, Apitherapy and Homeopathy. Assessment of the Module: The course comprises two types of assessments; continuous and final assessment. Continuous assessments toke place throughout the course. They are mostly based on course work as follows; Seminar (10%), Assignments (10%), Field visit report (10%) and Mid-term exam (20%). A proportion of 50% was taken in the final assessment. A student who scored 60 or more deemed to have passed this course. Conclusion: The feedback received was most supportive of the module and appreciative of the teachers, the information provided and skills gained and the way in which it was delivered.